Adenomyosis in Pregnancy—Should It Be Managed in High-Risk Obstetric Units? - Rodrigo Orozco; José Carlos Vilches; Ignacio Brunel; Manuel Lozano; Gema Hernández; David Pérez-Del Rey; Laura Meloni; Juan Luis Alcázar (Diagnostics, 2023)
Background: Uterine adenomyosis is an increasingly frequent disorder. Our study aimed to demonstrate the presence of obstetric complications in the population affected by this condition to demonstrate the need for follow-up in high-risk obstetric units. Material and Methods: The data for the study were obtained from TriNetX, LLC, between 2010 and 2020. The outcomes analyzed were intrauterine growth restriction (IUGR), preterm delivery, cesarean delivery, hypertension, abruption placentae, and spontaneous abortion. Seven thousand six hundred and eight patients were included in the cohort of pregnant patients with adenomyosis, and 566,153 women in the cohort of pregnant patients without any history of endometriosis. Results: Upon calculating the total risk of presenting any of these problems during pregnancy, we obtained an OR = 1.521, implying that a pregnancy with adenomyosis was 52.1% more likely to present some complication. We found: IUGR OR = 1.257 (95% CI: 1.064–1.485) (p = 0.007); preterm delivery OR = 1.422 (95% CI: 1.264–1.600) (p = 0.0001); cesarean delivery OR = 1.099 (95% CI: 1.002–1.205) (p = 0.046); hypertensive disorders OR = 1.177 (95% CI: 1.076–1.288) (p = 0.0001); abruption placentae OR = 1.197 (95% CI: 1.008–1.422) (p = 0.040), and spontaneous abortion OR = 1.529 (95% CI: 1.360–1.718) (p = 0.0001). Conclusion: We conclude that the review carried out and the data we obtained on increased risk provide sufficient evidence to recommend that patients with adenomyosis should be managed in obstetric high-risk units.